1999
DOI: 10.1042/bj3420431
|View full text |Cite
|
Sign up to set email alerts
|

Anionic phospholipids decrease the rate of slippage on the Ca2+-ATPase of sarcoplasmic reticulum

Abstract: Accumulation of Ca2+ by the Ca2+-ATPase of skeletal-muscle sarcoplasmic reticulum has been measured in reconstituted, sealed vesicles as a function of lipid composition. Measurements were performed in the presence of carbonyl cyanide p-trifluoromethoxyphenylhydrazone (FCCP) to eliminate any effects of H+ transport; in the presence of FCCP, addition of valinomycin had no effect on the level or rate of accumulation of Ca2+ showing that, in the presence of FCCP, no electrical potential built up across the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…The rate of rotational diffusion of SLN within the lipid bilayer is inversely proportional to the cube of the transmembrane diameter of the rotating species. Synthetic SLN, with the ␣-position of residues Tyr 29 and Tyr 31 labeled with 13 C and the ␣-position of Val 19 labeled with 2 H, was incorporated into DOPC membranes, and the overall rotational mobility of SLN was probed using 13 C and 2 H solid-state magicangle spinning (MAS) NMR experiments. The spectra are sensitive to motional averaging of the 2 H quadrupolar anisotropy or the 1 H- 13 C dipolar anisotropy as a result of rotational diffusion of SLN with a rotational correlation time R SLN in the range 10 Ϫ4 -10 Ϫ6 s. The spectra indicated that neither the dipolar and quadrupolar anisotropies were scaled markedly by motional averaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of rotational diffusion of SLN within the lipid bilayer is inversely proportional to the cube of the transmembrane diameter of the rotating species. Synthetic SLN, with the ␣-position of residues Tyr 29 and Tyr 31 labeled with 13 C and the ␣-position of Val 19 labeled with 2 H, was incorporated into DOPC membranes, and the overall rotational mobility of SLN was probed using 13 C and 2 H solid-state magicangle spinning (MAS) NMR experiments. The spectra are sensitive to motional averaging of the 2 H quadrupolar anisotropy or the 1 H- 13 C dipolar anisotropy as a result of rotational diffusion of SLN with a rotational correlation time R SLN in the range 10 Ϫ4 -10 Ϫ6 s. The spectra indicated that neither the dipolar and quadrupolar anisotropies were scaled markedly by motional averaging (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two reconstitution compositions were examined, one with a lipid/ PLB/Ca 2ϩ -ATPase ratio of 500:20:1 and one with a lipid/PLB/ Ca 2ϩ -ATPase ratio of 160:10:1. Fast-twitch skeletal muscle (SERCA1) Ca 2ϩ -ATPase was reconstituted alone or with synthetic null-cysteine PLB into unsaturated lipid (DOPC) membranes using an adaptation of a previously described procedure (29). SERCA1 was examined instead of the cardiac isoform because skeletal muscle readily yields sufficient (milligram) quantities of enzyme for NMR analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Co-reconstitution of Ca 2ϩ -ATPase with PLB-Co-reconstitution of Ca 2ϩ ATPase and PLB were carried out by an adaptation of a previous method (8,29). Initial molar ratios of DOPC/PLB/Ca 2ϩ -ATPase were 500:20:1 or 160:10:1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of detergent by the addition of SM 2 Bio-Beads led to the formation of tightly sealed vesicles containing the Ca 2ϩ -ATPase (26). The reconstituted vesicles are impermeable to ATP so that only outwardly facing ATPase molecules hydrolyze ATP added to the external medium.…”
mentioning
confidence: 99%